Optimal Coordinated Charging of Electrical Vehicles Using Binary Integer Linear Programming - Liu, Yuanbin; Gao, Shuhua; Yue, Renfeng; Fan, Xuezhong; Li, Congcong; Kong, Lingxin; Zhou, Xiaoyu (Chinese Control Conference, 2023)
This paper investigates coordinated charging of electrical vehicles (EVs) that aims to minimize the charging expenses subject to various constraints. In particular, AC (Alternating Current) charging poles popular in old-fashioned apartment complexes are considered. The unique character of this problem setting is the discrete ON/OFF action instead of continuous power adjustment widely studied in the literature. We formulate such coordinated charging as a binary integer linear programming problem and solve it with a mature off-the-shelf solver for its high efficiency and global optimality. Finally, simulation experiments with 100 EVs are carried out, and results show that the proposed approach outperforms other widely-used methods in terms of charging cost reduction and constraint satisfaction.